Avaliação da Rigidez Arterial Central em Idosos não Hipertensos: Estudo Longitudinal - Pereira, Cristiane de Sousa (2021)
Introduction: Numerous cardiovascular risk factors, including aging and Systemic Arterial Hypertension (SAH), can modify the functional and structural properties of the cardiovascular system. Prehypertension in the elderly could be differentiated from non-prehypertensive states through the structural characteristics of the wall of the great arterial vessels. Objective: This retrospective coort study aimed to verify the possible differences in central arterial stiffness and its evolution among older adults with optimal blood pressure (OBP), normal blood pressure (NBP), and prehypertension (PH). Methods: We analyzed the database of the Study of Pulse Wave Velocity and Peripheral Pressures in Older Adults in Urban Areas in Brazil (EVOPIU study). We included 110 normotensive patients without comorbidities and evaluated them in two visits (V1 and V2), with an interval of 35.6 ± 12.6 months. The patients were separated them into three groups according to systemic blood pressure (SBP) values: OBP, systolic pressures (SP) <120 and diastolic pressures (DP) <80 mmHg), (n = 33); NBP, (SP 120–129 and/or DP 80–84 mmHg), (n = 44); and PH, (SP 130–139 and/or DP 85–89 mmHg), (n = 33). Clinical and laboratory data, central and peripheral pressures, and the carotid-femoral pulse wave velocity (cf-PWV) in V1 and V2 were obtained. Results: For the OBP group, the cf-PWV was from 8.74 ± 0.44 m/s to 10.51 ± 0.42 m/s (P < 0.05), with a progression rate of 0.063 ± 0.016 m/s; for the NBP group, the cf-PWV was 7.96 ± 0.35 m/s to 10.10 ± 0.35 m/s, with a progression rate of 0.065 ± 0.014; and for the PH group, the cf-PWV was from 8.48 ± 0.42 m/s to 10.98 ± 0.41 m/s, with a progression rate of 0.057 ± 0.019. Conclusions: Elderly patients with OBP had central arterial stiffness and cf-PWV progression rates like patients with NBP and PH.